The prevalencce of certain risk factors of non-communicable diseases in a rural community : a physiotherapeutic perspective - Van Rooijen, Agatha Johanna (University of Pretoria, 2013)
Dissertation (MSc (Physiotherapy Management))--University of Pretoria, 2005.